Improved Prodigiosin Production by Relieving CpxR Temperature-Sensitive Inhibition - Sun, Yang; Wang, Lijun; Pan, Xuewei; Osire, Tolbert; Fang, Haitian; Zhang, Huiling; Yang, Shang-Tian; Yang, Taowei; Rao, Zhiming (Frontiers in Bioengineering and Biotechnology, 2020)
Prodigiosin is a typical secondary metabolite mainly produced by Serratia marcescens. CpxR protein is an OmpR family transcriptional regulator in Gram-negative bacteria. Firstly, it was found that insertion mutation of cpxR in S. marcescens JNB 5-1 by a transposon Tn5G increased the production of PG. Results from EMSA indicated that CpxR could bind to the promoter of the pig gene cluster and repressing the transcription levels of genes involved in PG biosynthesis in S. marcescens JNB 5-1. In the △cpxR mutant strain, the transcription levels of the pig gene cluster and the genes involved in pathways of PG precursors such as proline, pyruvate, serine, methionine, S-adenosylmethionine were significantly increased, hence promoting the production of PG. Subsequently, a fusion segment composed of genes proC, serC and metH responsible for proline, serine and methionine was inserted into the cpxR gene in S. marcescens JNB 5-1. On fermentation by the resultant engineered S. marcescens, the highest PG titer reached 5.83 g/L and increased by 41.9%, relative to the parental strain. In this study, we revealed the role of CpxR in PG biosynthesis and provided an alternative strategy for engineering of S. marcescens to enhance PG production.